2020
DOI: 10.1177/0844562120908747
|View full text |Cite
|
Sign up to set email alerts
|

Detriments of a Self-Sacrificing Nursing Culture on Recruitment and Retention: A Qualitative Descriptive Study

Abstract: Aim To investigate the presence and impact of self-sacrifice within the nursing profession. Background Evidence suggests the existence of a culture of self-sacrifice within nursing, but its potential detriments to the profession have not been explored. Design A qualitative descriptive approach was used. Methods Semistructured interviews were conducted with 10 practicing nurses to explore the existence and potential implications of a self-sacrificing culture within nursing. Results All participants reported sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In this regard, a study has emphasized the necessity of attention to health promotion programs and preventive intervention in the workplace, considering the significant psychological impact the COVID-19 crisis has had on healthcare workers; this study recommended that policy-makers plan interventions, including supplying pertinent information and psychosocial support, acknowledging success, increasing resilience, and monitoring the health status of staff ( 37 ). Studies have also shown that the culture of self-sacrifice leads to increased physical and emotional exhaustion in the nurse’s workplace ( 3 ). According to studies, occupational stress, whether accompanied by workplace violence or not, increases the risk of harm associated with facing violence ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, a study has emphasized the necessity of attention to health promotion programs and preventive intervention in the workplace, considering the significant psychological impact the COVID-19 crisis has had on healthcare workers; this study recommended that policy-makers plan interventions, including supplying pertinent information and psychosocial support, acknowledging success, increasing resilience, and monitoring the health status of staff ( 37 ). Studies have also shown that the culture of self-sacrifice leads to increased physical and emotional exhaustion in the nurse’s workplace ( 3 ). According to studies, occupational stress, whether accompanied by workplace violence or not, increases the risk of harm associated with facing violence ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are valuable assets of the health system who work in the frontline of health care provision during the pandemic; this means that they are the personnel most affected by it ( 2 ). The nursing profession is inseparable from values such as “empathy, love, and self-sacrifice,” so a culture of self-sacrifice has become an integral element of this occupation ( 3 ). In spite of the harsh conditions, nurses make sacrifices, provide for patients’ needs, and disregard their own needs and wellness, spending all their power on providing quality care and fulfilling patients’ needs ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The considerate level of IR among Chinese nurses predicted a relatively adequate nursing workforce to be arranged in future infectious disease emergency events. Moreover, related studies highlighted a culture of self‐sacrifice in the nursing profession may lead to job dissatisfaction, presenteeism, burnout and retention problems (Ciezar‐Andersen & King‐Shier, 2020). As a result, there is no need to force a small number nurse who was reluctant to respond at the legal level.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have suggested the role of self-sacrifice in this regard [11,12]. We believe that in healthcare professionals, this factor can be considered a reason for not leaving the duty not only despite the insufficient personal protective equipment but also death in the way of treatment of patients.…”
Section: Dear Editor In Chiefmentioning
confidence: 86%